Search for a charged Higgs boson decaying into a heavy neutral Higgs boson and a W boson in proton-proton collisions at √s = 13 TeV - Tumasyan, Armen (2023)
A search for a charged Higgs boson H± decaying into a heavy neutral Higgs boson H and a W boson is presented. The analysis targets the H decay into a pair of tau leptons with at least one of them decaying hadronically and with an additional electron or muon present in the event. The search is based on proton-proton collision data recorded by the CMS experiment during 2016–2018 at √s = 13 TeV, corresponding to an integrated luminosity of 138 fb−1. The data are consistent with standard model background expectations. Upper limits at 95% confidence level are set on the product of the cross section and branching fraction for an H± in the mass range of 300–700 GeV, assuming an H with a mass of 200 GeV. The observed limits range from 0.085 pb for an H± mass of 300 Ge V to 0.019 pb for a mass of 700 GeV. These are the first limits on H± production in the H± → HW± decay channel at the LHC.